The effects of changing western worldviews on morals and ethics in economics: a protestant perspective - Appalraju, Nerusha (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
The World Economics Association held an online conference in 2012 where they published many papers on ethics in economics. The topic of ethics in economics became more serious and popular following the 2008 financial crisis. However the case for a professional code of ethics in economics is difficult to introduce and implement due to the multidisciplinary approach of the discipline. Therefore authors such as Dow (2012), De Martino (2012), Freeman (2012) and Earl (2012) urged economists to start thinking about ethics in economics from a pluralistic view. This thesis studied the effects of changing Western worldviews on morals and ethics in economics from a Protestant perspective. Numerous authoritative sources were considered and used to create a discussion and analysis of how diverse Western worldviews impact on the type of economics which is prescribed and practiced. It was found that different Western worldviews create various standards of understanding and evaluation, which result in varying opinions on what constitutes as morally or ethically acceptable within the discipline of economics.
Keywords: Economics -- Moral and ethical aspects; Neoclassical school of economics; Capitalism -- Religious aspects -- Protestant churches; Feminist economics; Economics -- Religious aspects; Environmental economics -- Moral and ethical aspects; Smith, Adam, 1723-1790; Weber, Max, 1864-1920